Investigating the key controls on mine water temperature in the United Kingdom - Receveur, Mylène (The University of Edinburgh, 2024)
Following the 2015 Paris Climate Agreement, the UK Government announced that gas boilers will be banned in all new homes from 2025. Among the developing low-carbon energy sources available to decarbonise residential and commercial heating across the UK, the thermal energy within abandoned, flooded coal mines has significant potential. Mine workings access a large volume of rock and are easily accessible from the surface. With 25% of the UK population living over legacy workings, they also represent an opportunity to reduce fuel poverty in deprived rural areas within former coalfields. Understanding what determines the temperature of mine-water is essential to characterise the heat available and accessible by mine-water heating systems in the long-term, and therefore promote the development of the resource in the UK. This research aims to characterise the key controls on the mine-water temperature (MWT) in UK coalfields and the mechanisms of heat recharge. These aims are first constrained through the compilation of monitoring data available from The Coal Authority in a geodatabase, which includes temperature profiles, temperature and water level times series, flow rate and discharge rate measurements. Each acquisition was associated with the status of the mine-water block (MWB) at the time of acquisition, the site characteristics (e.g. location, type of site), mine history (e.g. abandonment date) and historic temperature measurements available from the literature. The data analysis highlighted a clear linear relationship between the average MWT in pumping and monitoring shafts and the average depth of the observations. Discrepancies in MWT observed between different sites within the same coalfield were then investigated numerically by looking at the effect of a range of thermal and hydraulic properties, pumping scenarios, hydraulic recharge scenarios and geometrical parameters on the temperature distribution and heat extraction rate in mines, considering models of simple geometries. Solutions for groundwater flow and heat transfer equations were calculated using the opensource finite-element numerical modelling software OpenGeoSys. The results indicated the key effects of the pumping depth relative to the seam depth and the nature of hydraulic recharge. The latter was shown to significantly alter the temperature distribution in the pumping and monitoring shafts, both during pumping and water rebound. Subsequently, the nature and temperature of recharging mine water were shown to determine the extent of the thermal disturbances following a period of dewatering and water rebound, with the discrepancies between the observed and predicted geothermal gradient decreasing with time since the mine abandonment. Although the permeability of longwall panels was suggested to not significantly impact the thermal steady-state conditions, transient analyses revealed the key control of the permeability contrasts between the mined-out area and the surrounding fractured media on the rate at which heat is mined from the rock and conveyed to the shaft. Additionally, the total recoverable heat from a mine-water reservoir was highly influenced by the total thickness of the mined area. Mine-water reservoirs are highly complex geometrical and hydraulic systems and are subject to numerous uncertainties, due to the long history of mining, poor mapping and documentation, and the inability to characterise the current state of the mine workings. Hence, no standard modelling approach to quantify the potential thermal resource available has yet been developed. To that aim, a numerical model for the Dawdon High Main seam in the area surrounding the pumping Theresa shaft in the NE England Coalfield, UK, was finally developed to investigate the effect of geometrical simplifications on the heat potential assessment for more complex mine workings including open roadways, pillar-and-stall and longwall panels. Results showed that appropriate estimates of the long-term heat potential of mines can be undertaken for large-scale studies using equivalent porous media approaches, which simplify the model development process and decrease the computational time. In conclusion, this research has successfully characterised the key controls on MWT and the key features controlling the heat distribution and heat extraction rate in mines. This provides insights into the essential parameters to consider when assessing the heat potential of flooded coal mines, with the ultimate aim of contributing to the development of a generic conceptual tool for the assessment of the sustainable rate of heat recovery, both in the UK and beyond. This includes the potential to develop a method based on calculations of the relative distribution of permeability and porosity for individual mining depth intervals.
Keywords: Mine-Water Heat; Coal Mines; Temperature Profiles; Numerical Modelling; OpenGeo- Sys